DESIGN OF EXPERIMENT (DOE) LIQUID PHOTOIMAGEABLE SOLDER MASKS PCB PADA TEACHING FACTORY MANUFACTURING OF ELECTRONICS (TFME) POLITEKNIK NEGERI BATAM - Nadhrah Wivanius; Nur Sakinah Asaad; Heru Wijanarko; Ira Zamzami (JURNAL INTEGRASI, 2020)
This paper examines several variables to formulated the best parameters in the PCB manufacturing process. This study was implements a PCB with a screen printing process that uses the LPISM (Liquid Photoimageable Solder Mask) application. Where in the process PCB coating is done by connecting the amount of solder liquid mask in one coating using the right parameters using the Design of Experiment (DoE) method. This DoE method improves the quality of the PCB at the lowest possible cost. DoE on LPISM applied at the Teaching Factory Manufaktur Elektronika Politeknik Negeri Batam with the aim of protecting the PCB lines from being connected to one another, providing the right measurements, and using the use of laminated mask solder. Thus, Politeknik Negeri Batam Teaching Factory laboratory assistants can produce PCBs using the LPISM method with quality according to standards. From the analysis, obtained an appropriate angle for screen printing is between 150-200 so that the screen is not damaged. In addition, the oven process can thin the solder mask up to 70-80%. In accordance with the results of comprehensive testing, the 24th data obtained can be recommended because it fulfill the IPC-SM-840C standard, with the 2.5 μm solder mask thickness.